An Error Analysis Made by the Third Year English Department Students in Translating Hortatory Text - Mahaputri Winati; Rusdi Noor Rosa (Journal of English Language Teaching, 2021)
This study aims at finding out the types of errors made by the third year English Department students of Universitas Negeri Padang in translating a hortatory text from Bahasa Indonesia into English. This study used a descriptive method. The data were the translation of the hortatory text entitled Bersama Atasi Covid-19 done by the third year English Department students of Universitas Negeri Padang. The data were collected by using a test and were analysed using error analysis. The results of the study indicate that there are three types of errors which error of addition of meaning is the most error frequently committed by the students in their translation with the frequency of 84times (40.6%). Omission error (31.9%) is the second, while the error of deviation of meaning is the least error found in the students’ translation.